The clinical phenotype with gastrostomy and abdominal wall infection in a pediatric patient with Takenouchi-Kosaki syndrome due to a heterozygous c.191A > G (p.Tyr64Cys) variant in CDC42: a case report - Szczawińska-Popłonyk, Aleksandra; Popłonyk, Natalia; Badura-Stronka, Magdalena; Juengling, Jerome; Huhn, Kerstin; Biskup, Saskia; Bancerz, Bartłomiej; Walkowiak, Jarosław (Frontiers in Genetics, 2023)
The CDC42 (cell division cycle homolog 42) gene product, Cdc42 belongs to the Rho GTPase family which plays a pivotal role in the regulation of multiple cellular functions, including cell cycle progression, motility, migration, proliferation, transcription activation, and reactive oxygen species production. The Cdc42 molecule controls various tissue-specific functional pathways underpinning organogenesis as well as developmental integration of the hematopoietic and immune systems. Heterozygous c.191A>G (p.Tyr64Cys) pathogenic variants in CDC42 cause Takenouchi-Kosaki syndrome characterized by a spectrum of phenotypic features comprising psychomotor developmental delay, sensorineural hearing loss, growth retardation, facial dysmorphism, cardiovascular and urinary tract malformations, camptodactyly, accompanied by thrombocytopenia and immunodeficiency of variable degree. Herein, we report a pediatric patient with the Takenouchi-Kosaki syndrome due to a heterozygous p.Tyr64Cys variant in CDC42 manifesting as a congenital malformation complex accompanied by macrothrombocytopenia, poor specific antibody response, B and T cell immunodeficiency, and low serum immunoglobulin A level. We also suggst that feeding disorders, malnutrition, and a gastrointestinal infection could be a part of the phenotypic characteristics of Takenouchi-Kosaki syndrome supporting the hypothesis of immune dysregulation and systemic inflammation occurring in the p.Tyr64Cys variant in CDC42.